Pediculosis Capitis In Female Student's Life At Pondok Pesantren PPAI An-Nahdliyah Kabupaten Malang - Regina Rachmayanti Hapsari (Universitas Airlangga, 2021)
Background: Islamic boarding school dormitory has a high population density. This has resulted in high-potential of Islamic boarding schools in transmitting Pediculosis. All age groups can suffer from this disease, but children are more susceptible to the condition.Objective: The aims of this study was to analyze the relationship between the level of knowledge, personal hygiene, and characteristics of female students towards the presence of Pediculus humanus var. capitis in Islamic Boarding School An-Nahdliyah, Malang Regency.Methods: This research was quantitative research method, used observational analytic research with cross sectional design. The research sampe was 48 female students living in the dormitory, taken by simple random sampling. Data found at the time of the study was collected through questionnaires, observations, and laboratory tests. Determination of the type of flea species was tested at the Parasitology Laboratory, Faculty of Veterinary Medicine, Airlangga University. The sample in this study amounted to 48 female students living in dormitory of Islamic Boarding School An-Nahdliyah Malang Regency. This study has been declared to meet the ethical eligibility of the Medical Research Ethics Commission of the Faculty of Dentistry, Airlangga University with certificate number 161/ HRECC.FODM/ IV/ 2019.Result: The results showed that more than half of the sample (31 respondents) experienced Pediculus humanus var. capitis infestation. The results of this study indicate that there is no relationship between the level of education (p = 0,393), knowledge (p=0,55), length of stay (p=0,181), and hair type (p=0,464) on the existence of Pediculus humanus var. capitis. Though there is a relationship between personal hygiene (p = 0,001), age (p = 0,035), and hair length (p = 0,021).Conclusion: The conclusion of this study is personal hygiene, age, and hair length have a significant relationship to the Pediculus humanus var. capitis. Female students who experience Pediculus humanus var. capitis infestations can suffer from itching on the scalp as well as scalp irritation. It is recommended to improve female students' personal hygiene by routine shampooing three times a week, and using personal sleeping mats.